The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1017/s0021859600024874
|View full text |Cite
|
Sign up to set email alerts
|

Subjective assessment of body fat in live sheep

Abstract: Subjectively assessed body condition scores, determined on the live animal, were related to the percentages of chemical fat in the fleece-free empty bodies of 30 adult Scottish Blackface ewes. The results show that body condition scores can provide an acceptable and useful estimate of the proportion of fat in the live animal, and that the level of prediction is superior to that afforded by live weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
598
0
60

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,218 publications
(704 citation statements)
references
References 3 publications
8
598
0
60
Order By: Relevance
“…Many of the animal-based indicators suggested by this expert panel were focused on measures of flock health, for example, body condition scoring (BCS), lameness scoring, and skin lesion assessment. Although BCS was identified as a useful welfare assessment tool, and has been scientifically validated as a measure of the body fat content of sheep (Russel et al, 1969), the panel recognised that BCS was not an inappropriate indicator for young and growing animals. The panel also suggested that fewer categories of condition scores may be more appropriate for welfare assessment purposes.…”
Section: Welfare Issues Identifiedmentioning
confidence: 99%
“…Many of the animal-based indicators suggested by this expert panel were focused on measures of flock health, for example, body condition scoring (BCS), lameness scoring, and skin lesion assessment. Although BCS was identified as a useful welfare assessment tool, and has been scientifically validated as a measure of the body fat content of sheep (Russel et al, 1969), the panel recognised that BCS was not an inappropriate indicator for young and growing animals. The panel also suggested that fewer categories of condition scores may be more appropriate for welfare assessment purposes.…”
Section: Welfare Issues Identifiedmentioning
confidence: 99%
“…Ewe live weight (to the nearest 0.5 kg) and BCS (Russel et al, 1969) were recorded 1 week before mating, 6 weeks pre-lambing, 6 weeks post-lambing and at weaning. The permanent incisors of all ewes were assessed pre-mating for bite position, looseness, wear and general condition.…”
Section: Measurementsmentioning
confidence: 99%
“…Lambs were slaughtered when they attained a fat class of 2 to 3 (on a scale of 0 to 5), which was manually assessed by skilled technicians according to the method described by Russel et al (1969). The lambs had access to food and water until roughly 1 h before slaughter, and were transported by truck to the abattoir 25 km from the experimental site.…”
Section: Slaughter Proceduresmentioning
confidence: 99%
“…At 24 h post mortem, the carcass was weighed, graded for conformation using the commercial 15-point scale, as described by Fisher et al (2000), and assessed for external fat using the commercial 5-point scale (Russel et al, 1969). Carcass morphology was assessed by measuring carcass length, width of buttock, chest depth according to Fisher and de Boer (1994), and thorax and shoulder width according to Laville et al (2002).…”
Section: Carcass Measurementsmentioning
confidence: 99%